2014
DOI: 10.1186/s12912-014-0040-z
|View full text |Cite
|
Sign up to set email alerts
|

Is there a relationship between personality and choice of nursing specialty: an integrative literature review

Abstract: BackgroundPersonality is deemed to play a part in an individual’s choice of work, with individuals’ preferencing a profession or field of work that will satisfy their personal needs. There is limited research exploring the personality characteristics of nurses within clearly defined nursing specialty areas. Retaining nurses within specialty areas has workforce implications when vacancies are unable to be filled by appropriately experienced staff.The aim of the review was to determine the current state of knowl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 39 publications
2
25
0
Order By: Relevance
“…This is coherent with our comparative analysis. As previously mentioned, it also agrees with the results offered by authors who analysed the relationship between certain specialties and decision authority or personality (Adriaenssens et al, ; Kennedy et al, ; McPhail, ). The categories “clinical training” and “other” in the variable “continuous training” also appear to be related to a lower score in the somatic symptoms and anxiety–insomnia subscales of GHQ‐28.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This is coherent with our comparative analysis. As previously mentioned, it also agrees with the results offered by authors who analysed the relationship between certain specialties and decision authority or personality (Adriaenssens et al, ; Kennedy et al, ; McPhail, ). The categories “clinical training” and “other” in the variable “continuous training” also appear to be related to a lower score in the somatic symptoms and anxiety–insomnia subscales of GHQ‐28.…”
Section: Discussionsupporting
confidence: 91%
“…This fact was specifically addressed in our survey, and we found that 41.8% of nurses with a specialty/profile were in this situation. Our results may also be linked to the relationship between personality and specialty, covered in a recent scoping review (Kennedy, Curtis, & Waters, ). It has also been suggested that nurses feel attracted to a certain nursing specialty as a result of their personality (McPhail, ).…”
Section: Discussionmentioning
confidence: 64%
“…In addition, a literature review study (23) tried to find whether there was a relationship between personality and the specialty chosen by nursing professionals, and it suggested that there is evidence of a relationship between personality features, the specialty chosen, burnout and professional satisfaction. Bibliographic references about this topic were found to be limited and the effect of personality on the will to remain in the activity was not closely related.…”
Section: Quality Of Life and Mood Disorder In Nursing Professionals Omentioning
confidence: 99%
“…The meta-analysis by [Kennedy et al (2014a)] incorporates the data from only 13 scientific articles published in the years 1965-2010. The data were analysed from various theoretical and methodological viewpoints, which makes relevant comparisons almost impossible.…”
Section: The Current Studymentioning
confidence: 99%
“…The value of Holland's theoretical proposition lies in his integrated psychological and sociological approach which accounts for not only the personality type but also characteristics of the workplace environment, and, specifically, characteristic types of activities that make a good match (congruence) and translate into professional success and satisfaction (Pike, 2006). It is underlined that such congruence may be particularly important in medical professions preventing professional burnout and being conducive to continued practice of a given profession (Kennedy, Curtis, & Waters, 2014a).…”
Section: Introductionmentioning
confidence: 99%